Study of early perinatal outcome in lower segment caesarean section in severe foetal distress at tertiary care centre - Jadhav, Chandrakant A.; R., Tirankar V.; S., Gavandi P. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: For asphyxia, the fetus reacts with a series of responses. First there is redistribution of blood flow to vital centres to limit the deleterious effects of oxygen limitation in the brain, heart and adrenal glands. A further compensatory response is that overall fetal oxygen consumption declines to values as low as 50% of the control. Methods: This was a prospective study. Early perinatal outcome of newborns delivered through Caesarean section due to clinical foetal distress in labour was compared with a group of newborns similarly delivered via Caesarean section without a diagnosis of clinical foetal distress. Data collected and analysed using appropriate standard statistical methods i.e. Chi-square (X2) test and ‘Z’ - test. Results: Most common indication for NICU admission in study group was MAS (Meconium Aspiration Syndrome 14%) followed by MAS with perinatal asphyxia (5.33%), MAS with Hypoxic ischaemic encephalopathy (HIE) - stage III (3.33%) paerintal asphyxia (2.66%), severe PNA with HIE - III (0.66%) and TTN (0.66%) meconium gastritis (0.66%) respectively. Conclusions: Clinical foetal distress (study group) was found to be significantly associated with low 1 min and 5 min. Apgar score. There was no significant difference in immediate NICU admission whether D-D (i.e. detection fetal detection to delivery interval) time interval <30 minutes or >30 minutes. But rate of mortality was high when D-D (i.e. detection fetal detection to delivery interval) was >30 minutes.